A closer look at African soils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
No. 8. Participatory Research on Compost and Liquid Manure in Kenya (DD Onduru, GN Gachini, A De Jager, and J-M Diop. 1999. 28 pp.)